A review on multiplexing schemes for MIMO channel sounding - Ullah, Mohammad Habib; Priantoro, Akhmad Unggul (IJCSNS, 2009)
There are three multiplexing schemes for Multi-Input Multi-Output (MIMO) channel sounder Time-division multiplexing (TDM), Code-division multiplexing (CDM) and Frequency-division multiplexing (FDM). The purpose of this paper is comparison overview of multiplexing schemes for MIMO channel sounder. In this paper TDM, FDM and CDM techniques for MIMO channel sounding are considered. TDM, FDM and CDM multiplexing schemes have pros and cons in different aspects. The comparison between multiplexing techniques has been considered in terms of real-time measurement, hardware cost effectiveness and major drawbacks.